THE INNOVATIVE METHODS OF TEACHING ENGLISH GRAMMAR AT SECONDARY SCHOOL LEVEL (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article describes in detail the innovative methods of teaching English grammar at the secondary school level, the linguistic foundations of the English language teaching methodology in elementary grades, and the equal acquisition of speech and linguistic competences in English language teaching